2007
DOI: 10.1063/1.2802199
|View full text |Cite
|
Sign up to set email alerts
|

High repetition rate laser produced soft x-ray source for ultrafast x-ray absorption near edge structure measurements

Abstract: Recent progress in high intensity ultrafast laser systems provides the opportunity to produce laser plasma x-ray sources exhibiting broad spectrum and high average x-ray flux that are well adapted to x-ray absorption measurements. In this paper, the development of a laser based x-ray absorption near edge structure (XANES) beamline exhibiting high repetition rate by using the Advanced Laser Light Source (ALLS) facility 100 Hz laser system (100 mJ, 35 fs at 800 nm) is presented. This system is based on a broadba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Therefore, new source schemes have emerged in the last couple of decades such as high harmonics generation 6,7 and emission from dense plasmas. [8][9][10] High harmonic generation produces ultra-short coherent radiation with sub fs pulse duration and photon energies up to 2 keV. 11 However, the average photon flux of these sources in the water window is rather low 6 and in the 1 keV region with a flux of 10 5 ph/s in 0.1% bandwidth 11 still far from a level suitable for fluorescence applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, new source schemes have emerged in the last couple of decades such as high harmonics generation 6,7 and emission from dense plasmas. [8][9][10] High harmonic generation produces ultra-short coherent radiation with sub fs pulse duration and photon energies up to 2 keV. 11 However, the average photon flux of these sources in the water window is rather low 6 and in the 1 keV region with a flux of 10 5 ph/s in 0.1% bandwidth 11 still far from a level suitable for fluorescence applications.…”
Section: Introductionmentioning
confidence: 99%
“…Both discharge-plasmas 12,13 as well as laser-produced plasmas (LPPs) 8,10,14,15 are already a) Present address: ELI-DC AISBL, 23 Rue Montoyer, 1000 Brussels, Belgium. used in various generation schemes.…”
Section: Introductionmentioning
confidence: 99%
“…11 This XAFS technique has already been developed by different groups which had designed various kinds of spectrometers adapted to a specific energy range dependent on the studied system. [12][13][14][15] Several experiments have been recently performed taking advantage of this technique for the study of different dynamical processes: laser-shock compression of materials, 16 chemical reactions, 17 and solid-liquidplasma phase transitions, [18][19][20] to cite only a few. In each case, the characteristics required for the spectrometer are fixed by the energy range of interest and the parameters of the laser facility, as for example the repetition rate.…”
Section: Introductionmentioning
confidence: 99%
“…Other low repetition rate X-ray sources using ultrafast lasers to interact with the target material have been developed. Fourmaux et al reported recently on a new source working at a 100-Hz repetition rate with 30-fs duration and 100 mJ/pulse energy [50]. The emitted picosecond X-rays are in the soft X-ray region (100 to 1000 eV).…”
Section: Laser Plasma Sourcesmentioning
confidence: 99%